Comparative study of acid and alkaline pre-treatment process prior to gelatin extraction from rohu (Labeo rohita) scales - Abu Bakar, Muhammad Khairulnizam; Bakar, Jamilah; Zainal Abedin, Nur Hanani; Abdul Rahman, Russly; Syed Muhammad, Sharifah Kharidah (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2017)
Gelatin was extracted from rohu (Labeo rohita) scales using direct hot water extraction after different chemical pre-treatment using acid and alkaline. The aim of the study was to compare the extraction yield and physicochemical characteristics of gelatin obtained. The yield of gelatin extracted from acid pre-treated scales was 10.0 % (w/w) with gel strength 207.8 g, and viscosity 15.5 mPa·s, respectively whereas the yield of gelatin obtained from alkaline pre-treated scales was 7.1 % (w/w) with gel strength 180 g, and viscosity 7.7 mPa·s, respectively. The Fourier transform infrared (FTIR) spectra of both extracted gelatin showed similar absorption band characteristics.